Biosignal measures of female sexual interest: their feasibility in a forensic context. Issue 1 (12th March 2014) - Staunton, Ciara; Hammond, Sean; Perkins, Derek; Lambert, Sharon
Abstract : Purpose: – The purpose of this paper is to review the status of biosignal measures of female sexual arousal with a view to examining the feasibility of such procedures in a forensic context. Although adult women represent the minority of sexual offenders, female perpetrated sexual abuse has been gaining increasing attention in the forensic psychological literature as criminal justice is confronted with female offending populations to a greater extent than previously recognised. Design/methodology/approach: – Psychological assessments of sex offenders have tended to be over-dependent on the use of self-report measures (i.e. an individual's appraisal and report of their emotional state of sexual arousal). There is a dearth of empirical knowledge concerning the psychophysiological assessment of female sexual interest in general and especially so for female sex offenders. Physiological measures are those that rely on directly observable physiological responses of the individual in order to identify patterns of sexual interest or arousal. Findings: – Because deviant sexual interest (in children or the use of violence) as assessed by penile plethysmography, has been established as one of the strongest predictors of recidivism in male sex offenders (and as a viable alternative to self-report methodologies), an analogue measurement approach for female sex offenders is desirable. This paper considers: first, theoretical problems (e.g. what does female physiological arousal mean in terms of sexual arousal/desire?; second, technical measurement problems (e.g. reactivity of the measure in within subject designs); and third, procedural/ethical problems (e.g. invasiveness of the application). Originality/value: – While a number of physiological assessment devices are considered in this paper, the paper discusses the labial photoplethysmograph as a promising method for female sexual offender populations.